2017
DOI: 10.1002/cbm.2067
|View full text |Cite
|
Sign up to set email alerts
|

Screening for mental health needs of New Zealand youth in secure care facilities using the MAYSI‐2

Abstract: Young people in secure facilities in New Zealand have substantial service needs. Early intervention that engages them in services upon first contact with the youth justice system might help reduce this burden. Further validation of the MAYSI-2 in New Zealand may be warranted because of the unique ethnic make-up of these young offenders. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
10
0
2
Order By: Relevance
“…Even though this literature review focused on adolescents, all studies included different age ranges including children or young adults ( Table 2 ). Only one study focused on the general population ( 18 ), the rest of the studies investigated other adolescent population groups; young people in secure facilities ( 19 ), orphans ( 20 ), with cochlear implants ( 21 ), incarcerated ( 22 ), those held in custody ( 23 ) and from specific ethnic group; American Indians ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though this literature review focused on adolescents, all studies included different age ranges including children or young adults ( Table 2 ). Only one study focused on the general population ( 18 ), the rest of the studies investigated other adolescent population groups; young people in secure facilities ( 19 ), orphans ( 20 ), with cochlear implants ( 21 ), incarcerated ( 22 ), those held in custody ( 23 ) and from specific ethnic group; American Indians ( 24 ).…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of mental health needs was described by various aims in the different studies ( Table 2 ), in terms of describing the prevalence of probable mental health disorder and related needs ( 19 ), identifying mental health problems ( 20 ) or the trends in emotional and behavioral problems ( 18 ), in terms of emotional and behavioral strengths and difficulties ( 21 ), determining mental health and service needs ( 24 ), identifying the prevalence of mental disorders and mental health needs ( 22 ), and screening for mental health problems ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of mental health issues is even higher for youth in secure residences, and is estimated to be between 60-100% (The Werry Centre, 2009). Recent research into prevalence rates in Aotearoa New Zealand found that nearly 80% of young people in a youth justice residence had elevated scores on a mental health screening tool, the Massachusetts Youth Screening Instrument (second version, MAYSI-2), with higher rates for females and for Máori and Pacific Island subgroups (McArdle & Lambie, 2018).…”
Section: Original Articlementioning
confidence: 99%